2000
DOI: 10.1103/physrevb.63.012408
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic and transport properties of polycrystallineLa0.7Sr0.3Mn

Abstract: The effect of Fe doping (р10%) on polycrystalline samples of La 0.7 Sr 0.3 MnO 3 has been studied by means of x-ray diffraction, resistivity, ac susceptibility, magnetization, and magnetoresistance measurements. Fe doping does not affect the lattice structure, but it weakens the ferromagnetism and substantially augments the resistivity of the samples. The magnetoresistance of a sample with 10% Fe doping, in a 5 T magnetic field, was 4 times greater than that of the undoped sample near the peak in the resistivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 24 publications
2
33
0
Order By: Relevance
“…Some experimental work has already been done for these materials, [12][13][14][15][16] but from the present analysis we believe that several interesting features have not still been found experimentally. Specifically, we will show that, from the knowledge gained in the study of the phase diagrams of (La 1Ϫz RE z ) 1Ϫx Sr x MnO 3 and (La 1Ϫz RE z ) 1Ϫx Ca x MnO 3 , where RE is a trivalent rare earth, and from our model calculations, one can conclude that:…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…Some experimental work has already been done for these materials, [12][13][14][15][16] but from the present analysis we believe that several interesting features have not still been found experimentally. Specifically, we will show that, from the knowledge gained in the study of the phase diagrams of (La 1Ϫz RE z ) 1Ϫx Sr x MnO 3 and (La 1Ϫz RE z ) 1Ϫx Ca x MnO 3 , where RE is a trivalent rare earth, and from our model calculations, one can conclude that:…”
mentioning
confidence: 71%
“…Therefore it is a challenge to this model to give account of the experimental situation of the double series ͑1͒ in the range 0.3ϽxϽ0.5, [12][13][14][15][16] without stretching out the values of J AF already determined. 21,22,24 Ϫ1 with respect to the case y ϭ0.…”
Section: A Fe Substitutionmentioning
confidence: 99%
“…Takeuchi et al [16] suggested that Fe substitution for Mn dilutes the DE mechanism and shows typical spin glass and insulating behaviors. Several authors reported that Fe and Mn shows anti-ferromagnetic interaction in the Ln 1−x A x Mn 1−y Fe y O 3 compounds under the conditions of y ≤ x [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Mn site doping effects with transition elements have been extensively investigated [12,13]. The effects of substitution on the Mn site by other transition element is further known to affect the properties due to the changes produced in the average electron concentration and the shifts in the position of the e g and t g sub-bands.…”
Section: Introductionmentioning
confidence: 99%